Buffett's Alpha. Issue 4 (1st September 2018) - Frazzini, Andrea; Kabiller, David; Pedersen, Lasse Heje
Abstract : Warren Buffett's Berkshire Hathaway has realized a Sharpe ratio of 0.79 with significant alpha to traditional risk factors. The alpha became insignificant, however, when we controlled for exposure to the factors "betting against beta" and "quality minus junk." Furthermore, we estimate that Buffett's leverage is about 1.7 to 1, on average. Therefore, Buffett's returns appear to be neither luck nor magic but, rather, a reward for leveraging cheap, safe, high-quality stocks. Decomposing Berkshire's portfolio into publicly traded stocks and wholly owned private companies, we found that the public stocks have performed the best, which suggests that Buffett's returns are more the result of stock selection than of his effect on management. Abstract : A practitioner's perspective on this article is provided in the In Practice piece "Demystifying Buffett's Investment Success " by Keyur Patel. Disclosure: The authors are principals at AQR Capital Management, a global investment management firm, which may or may not apply investment techniques or methods of analysis similar to those described in this article. The views expressed here are those of the authors and not necessarily those of AQR. Editor's Note Submitted 24 April 2018 Accepted 15 June 2018 by Stephen J. Brown The original version had an error in Table 1, which has been corrected in this version.